Bosentan for pulmonary hypertension secondary to idiopathic pulmonary fibrosis. (2015) - Onda, Naomi; Tanaka, Yosuke; Hino, Mitsunori; Gemma, Akihiko
Abstract: Pulmonary hypertension is a poor prognostic factor in patients with interstitial lung disease. No established treatment exists for pulmonary hypertension secondary to interstitial pneumonia. We describe the case of an 81-year-old woman with idiopathic pulmonary fibrosis (IPF), who was admitted to our hospital due to aggravation of dyspnea and decreased oxygen saturation, as well as onset of orthopnea and rapidly progressing edema. The transthoracic echocardiography and right heart catheterization showed the mean pulmonary artery pressure was 39 mmHg and the mean pulmonary capillary wedge pressure was 9 mmHg. After various examinations, the diagnoses of pulmonary hypertension (PH) due to IPF and of congestive heart failure secondary to PH were established. Diuretic therapy was started, but the patient's condition showed poor improvement. Subsequent initiation of oral bosentan therapy led to improvement in symptoms and findings. At the follow-up assessment one year later her pulmonary function showed no significant changes and no apparent worsening of arterial blood gases, with evident improvement of PH, WHO functional class, maximum exercise tolerance on treadmill exercise testing, right heart catheterization, and transthoracic echocardiography. This report describes a case of successful treatment with bosentan for severe pulmonary hypertension in a patient with idiopathic pulmonary fibrosis. We also present a review of the literature on treatment of pulmonary hypertension in patients with chronic lung disease. Bosentan appears to be efficacious in some patients with pulmonary hypertension secondary to idiopathic interstitial pneumonitis.